استراتيجية واللعبة في الكلام العربية - Dian Ekawati (An Nabighoh Jurnal Pendidikan Dan Pembelajaran Bahasa Arab, 2017)
Learning is to transfer knowledge from educator to learners in a learning environment which has been deliberately created. In the process of learning, a right strategy is needed to acheve the expected goals. The same thing also goes to the process of learning Arabic which requires the right strategy tha is in accordance with the skills to be taught. Kalam learning strategy is a plan arranged to achieve the desired goals or objectives, that is the fluency of speaking Arabic of the students. The strategy is also one of the components in learning. A varied method of teaching is one of the ways to avoid boredom in learning. Kalam learning process variation can also use language games to provoke students to speak up Arabic more properly. Key word: learning strategy, a language game in learning kalam.